2022
DOI: 10.7150/ijms.77818
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Body Mass Index Stratification for the Prediction of Maximal Oxygen Uptake

Abstract: The purpose of this study was to investigate whether modeling within separate body mass index (BMI) stratifications improves the accuracy of maximal oxygen uptake (VO 2max ) prediction compared to a model developed regardless of adults' BMIs. A total of 250 Taiwanese adults (total group, TOG) aged 22-64 years participated in this study, and were stratified into a normal group (NOG: 135), an overweight group (OVG: 69), and an obesity group (OBG: 46), according to the BMI classification recommended by the Taiwan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have shown significant differences in cardiorespiratory fitness among adults with different BMI levels, with a higher BMI being associated with lower cardiorespiratory fitness 12 , 36 ; overweight or obesity may increase the risk of cardiovascular disease in the general population 37 , 38 ; and BMI and PBF are both important factors for the prediction of , with PBF being a more accurate predictor of than BMI 11 , 16 , 27 , 39 , 40 . All of these findings were confirmed by the results of this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown significant differences in cardiorespiratory fitness among adults with different BMI levels, with a higher BMI being associated with lower cardiorespiratory fitness 12 , 36 ; overweight or obesity may increase the risk of cardiovascular disease in the general population 37 , 38 ; and BMI and PBF are both important factors for the prediction of , with PBF being a more accurate predictor of than BMI 11 , 16 , 27 , 39 , 40 . All of these findings were confirmed by the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, participants also wore a suitable respirator mask, which was connected to a sampling line and a digital flow sensor to measure oxygen uptake ( ) and the content of produced carbon dioxide ( ). The initial load for the CPET was 25 W, with an increase of 15 W every two minutes (i.e., one stage every two minutes) until the participants could no longer maintain a pedalling frequency of 70 rpm 12 , 27 . At the same time, the Borg Rating of Perceived Exertion (RPE, 6–20) was used to ask participants about their level of fatigue during the CPET.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The classical method of estimating is during the incremental exercise test [ 3 , 24 , 25 , 26 , 27 ]. These studies focus on estimating the during the exercise intervention to investigate the long-term changes and monitor the performance and fitness of the individual.…”
Section: Related Workmentioning
confidence: 99%